Deploying Warrants, Producing Policy: A Self-Study of Teacher Education Policy Discussions. Issue 3 (2nd September 2019) - Cuenca, Alexander
ABSTRACT: The practice of teacher education is inextricably linked to the policy environment in which it occurs. Calls by policymakers and politicians for accountability measures, standardization and performance assessments are efforts to influence the direction of the preparation of educators. In this self-study, I examine my participation in a state-level teacher education policy decision-making body in the United States in order to illuminate how policy decisions are made about teacher education. More specifically, I discuss the kinds of warrants about teacher education practice that I deployed as I navigated the political and practical consequences of policy decisions. This study serves not only to illuminate the nature of policy discussions in teacher education, but also to encourage teacher educators to engage directly the policy-making arenas that implicitly and explicitly influence their work.